Implementing cognitive rehabilitation for people with Multiple Sclerosis: translating research into clinical practice - Mhizha-Murira, Jacqueline Rufaro (2019)
People with multiple sclerosis frequently report cognitive problems, which can affect function and quality of life. Although the effectiveness of cognitive rehabilitation to address these problems is evaluated in research studies, inadequate reporting of the content of the interventions may hamper clinical implementation. This research aimed to explore avenues to increase the clinical impact of trials of cognitive rehabilitation through the development of a clinicianinformed, evidencebased checklist to guide researchers to better report cognitive rehabilitation studies in MS. The overarching design was exploratory mixed-methods, involving three separate intertwining studies.